2016
DOI: 10.1017/s0033291716001719
|View full text |Cite
|
Sign up to set email alerts
|

Childhood bullying victimization is associated with use of mental health services over five decades: a longitudinal nationally representative cohort study

Abstract: Background. Research supports robust associations between childhood bullying victimization and mental health problems in childhood/adolescence and emerging evidence shows that the impact can persist into adulthood. We examined the impact of bullying victimization on mental health service use from childhood to midlife.Method. We performed secondary analysis using the National Child Development Study, the 1958 British Birth Cohort Study. We conducted analyses on 9242 participants with complete data on childhood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 32 publications
1
55
0
10
Order By: Relevance
“…In one of these studies with follow‐up at 12 and 36 weeks, the cost‐effectiveness findings reversed between the two time‐points: the shorter follow‐up suggested SSRI treatment was more cost‐effective, whereas the longer follow‐up showed that SSRI plus CBT was more cost‐effective. An illustrative example of the enduring impact of childhood mental health problems is the long‐term consequences of bullying that can be observed in adulthood, requiring long‐term follow‐up to understand the economic aspects of interventions on these consequences.…”
Section: Current Economic Evidence and Key Events In Mental Health Carementioning
confidence: 99%
“…In one of these studies with follow‐up at 12 and 36 weeks, the cost‐effectiveness findings reversed between the two time‐points: the shorter follow‐up suggested SSRI treatment was more cost‐effective, whereas the longer follow‐up showed that SSRI plus CBT was more cost‐effective. An illustrative example of the enduring impact of childhood mental health problems is the long‐term consequences of bullying that can be observed in adulthood, requiring long‐term follow‐up to understand the economic aspects of interventions on these consequences.…”
Section: Current Economic Evidence and Key Events In Mental Health Carementioning
confidence: 99%
“…Previous research, including a recent systematic review and meta-analysis, has established a robust association between global assessments of bullying and a number of detrimental mental health outcomes in adolescence and over the life course (Arseneault 2017;Haraldstad et al 2016;Moore et al 2017;Troop-Gordon 2017). For example, bullying victimization is associated with self-harming behaviour (Bucchianeri et al 2014), lower self-esteem and quality of life (Bucchianeri et al 2014;Haraldstad et al 2016), depressive symptoms (Bucchianeri et al 2014;Cole et al 2016;Fahy et al 2016;Gámez-Guadix et al 2013;Hill et al 2017;Lemstra et al 2012;Puhl and Luedicke 2012;Turner et al 2013), anxiety symptoms (Fahy et al 2016), substance use (Mackie et al, 2011;Radliff et al 2012;Turner et al 2018), suicidal behaviours (Litwiller and Brausch 2013;Moore et al 2017;Skapinakis et al 2011), and mental health service use (Evans-Lacko et al 2017). As well, previous research has indicated that experiences of bullying in childhood and adolescence are related to an increased likelihood of mental disorders in adulthood (Copeland et al 2013;Lund et al 2008;Sigurdson et al 2014;Takizawa et al 2014).…”
Section: Victimization Experiences and Mental Healthmentioning
confidence: 99%
“…We controlled for childhood confounders known to be associated with bullying, and with the outcomes under study (Takizawa et al, 2014;Evans-Lacko et al, 2016). Childhood IQ was assessed at age eleven using a standardized 80-item general ability test (Douglas, 1964).…”
Section: Childhood Confoundersmentioning
confidence: 99%
“…Wolke and Lereya, 2015;Arseneault, 2017). Relatedly, it is not surprising that childhood bullying victimisation is associated with increased mental health service use in childhood, adolescence, and early and mid-adulthood up to age 50 (Evans-Lacko et al, 2016;Sourander et al, 2009;Sourander et al, 2016).…”
Section: Introductionmentioning
confidence: 99%